2021
DOI: 10.1101/2021.10.28.466336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping neurotransmitter systems to the structural and functional organization of the human neocortex

Abstract: Neurotransmitter receptors support the propagation of signals in the human brain. How receptor systems are situated within macroscale neuroanatomy and how they shape emergent function remains poorly understood, and there exists no comprehensive atlas of receptors. Here we collate positron emission tomography scans in >1200 healthy individuals to construct a whole-brain 3-D normative atlas of 18 receptors and transporters across 9 different neurotransmitter systems. We find that receptor profiles align with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(99 citation statements)
references
References 171 publications
(206 reference statements)
2
93
0
Order By: Relevance
“…Spatial correlation between Covid19 severity-induced cerebrovascular burden map and spatial patterns associated with a range of neurotransmitter receptor/transporters (Hansen et al, 2021b), selective genes relevant to SARS-CoV-2 brain entry (Iadecola et al, 2020) and brain metabolism parameters (Vaishnavi et al, 2010). Neurotransmitter receptors and transporters were selective to serotonin (5-HT1a, 5-HT1b, 5-HT2a, 5-HT4, 5-HT6, 5-HTT), norepinephrine (NET), histamine (H3), acetylcholine (ACh, A4B2, M1, VAChT), cannabinoid (CB1), opioid (MOR), glutamate (mGluR5), GABA (GABAa/bz) and dopamine (D1, D2, DAT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial correlation between Covid19 severity-induced cerebrovascular burden map and spatial patterns associated with a range of neurotransmitter receptor/transporters (Hansen et al, 2021b), selective genes relevant to SARS-CoV-2 brain entry (Iadecola et al, 2020) and brain metabolism parameters (Vaishnavi et al, 2010). Neurotransmitter receptors and transporters were selective to serotonin (5-HT1a, 5-HT1b, 5-HT2a, 5-HT4, 5-HT6, 5-HTT), norepinephrine (NET), histamine (H3), acetylcholine (ACh, A4B2, M1, VAChT), cannabinoid (CB1), opioid (MOR), glutamate (mGluR5), GABA (GABAa/bz) and dopamine (D1, D2, DAT).…”
Section: Resultsmentioning
confidence: 99%
“…We further assessed the spatial overlap between COVID-19-related cerebrovascular burden maps and a range of brain metabolic, neurotransmitter, protein expression and cell-type parameters, including i) existing receptor/metabolic templates and ii) gene transcription profiling maps. Templates of interest included metabolic rates of glucose, oxygen, and aerobic glycolysis (Vaishnavi et al, 2010) and receptor and transmitter maps across nine different neurotransmitter systems (Hansen et al, 2021b), all measured by positron emission tomography (PET). Gene expression maps (Hawrylycz et al, 2012) were based on key proteins implicated in SARS-Cov-2 cellular attachment (angiotensin converting enzyme-2, ACE2; neuropilin-1, NRP1; neuropilin-2, NRP2), processing (cathepsin-B, CTSB; cathepsin-L, CTSL) and viral defence (interferon type 2 receptors, IFNAR2; lymphocyte antigen 6-family member E, LY6E) (Iadecola et al, 2020; Yang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We found that segregation is a signature of in-task performance, showing a link between functional network topology and behavior. Finally, under the hypothesis that nicotine decreases global correlations, we verified if the regional density of cholinergic-related receptors obtained by positron emission tomography (PET) [36][37][38][39][40][41] correlates with regional changes in FC. We observed that changes in nodal strength correlate with both the nodal SC strength, and the regional density of the α 4 β 2 nicotinic acetylcholine receptor.…”
Section: Introductionmentioning
confidence: 90%
“…To assess this possibility, we tested if the regional density of cholinergic-related receptors can explain the effects of nicotine on FC. We used regional density maps, obtained with PET [36][37][38][39][40][41], to test what acetylcholine-related receptors are associated with the changes in FC observed in the empirical data. Specifically, we considered density maps -parcellated using AAL90-for the α 4 β 2 nicotinic receptor, the M 1 muscarinic receptor, and the vesicular acetylcholine transporter (VAChT).…”
Section: Nicotinic Receptors Partially Mediate the Changes In Functio...mentioning
confidence: 99%
See 1 more Smart Citation